2013
DOI: 10.2519/jospt.2013.4349
|View full text |Cite
|
Sign up to set email alerts
|

Falls Among Patients Who Had Elective Orthopaedic Surgery: A Decade of Experience From a Musculoskeletal Specialty Hospital

Abstract: Study Design Retrospective cohort study. Objective To evaluate falls among elective orthopaedic inpatients at a musculoskeletal hospital. Background Falls are the most commonly reported hospital incidents. Approximately 30% of in-hospital falls result in minor injury, and up to 8% of falls result in moderate to severe injury. Given the projected rise in elective orthopaedic procedures, it is important to better understand fall patterns in this population. Methods A retrospective review of electronic medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Most in-hospital falls are caused by an interaction between environmental and patient-related risk factors (12). Many studies have looked at environmental risk factors and circumstances for in-hospital falls (5,8,12,13). Other studies have identified associations between patients with in-hospital falls and level of comorbidity (4,14), medication (8,(15)(16)(17), general muscle weakness and problems with balance (8,(15)(16)(17), fall history (8) and confusion (4,7,8,13,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Most in-hospital falls are caused by an interaction between environmental and patient-related risk factors (12). Many studies have looked at environmental risk factors and circumstances for in-hospital falls (5,8,12,13). Other studies have identified associations between patients with in-hospital falls and level of comorbidity (4,14), medication (8,(15)(16)(17), general muscle weakness and problems with balance (8,(15)(16)(17), fall history (8) and confusion (4,7,8,13,(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…L'instabilité du membre inférieur peut être également due à la douleur qui agit en inhibant l'action des muscles stabilisateurs du genou (réflexe nociceptif en flexion). En chirurgie orthopé-dique sans aucune précision des techniques anesthésiques, le taux de chute était de 0,9 % soit 2 chutes pour 1000 jours d'hospitalisation (868 chutes sur une période de 10 ans) [24]. Pour les patients opérés d'une prothèse articulaire de hanche ou de genou, cela représentait 0,85 %, soit 2,1 chutes pour 1000 jours d'hospitalisation [25].…”
Section: Risque De Chuteunclassified
“…Falls are common in the elderly, both in and out of hospital,17 with potential severe consequences, including fractures and other injuries, as well as more lasting effects, such as disability and fear of falling 2,8. Studies have found in-hospital fall rates after elective orthopedic surgery of about 1%,1,2,4 related to age, gender, and comorbidity1,4 or the use of femoral local anesthetic neural blockade 1,9.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found in-hospital fall rates after elective orthopedic surgery of about 1%,1,2,4 related to age, gender, and comorbidity1,4 or the use of femoral local anesthetic neural blockade 1,9. Several studies have tried to identify patient characteristic and circumstances associated with falling,3,5,10 to develop strategies for fall-prevention in community dwellers and medical patients3,11 but not in elective arthroplasty patients after discharge.…”
Section: Introductionmentioning
confidence: 99%